125k views
1 vote
Convert the expression (5x + 2)(x - 7) from factored form to standard form

User Verv
by
5.3k points

2 Answers

5 votes

Answer:

(5x + 2)(x - 7) = 5x² - 33x - 14

Explanation:


(5x+2)(x-7)=\\\\=(5x)(x)+(5x)(-7)+(2)(x)+(2)(-7)=\\\\=5x^2-35x+2x-14=\\\\=5x^2-33x-14

User Surendra Jnawali
by
5.2k points
0 votes
We use the FOIL method here. First, Outer, Inner, and Last.

(5x)(x) = 5x^2

(5x)(-7) = -35x

(2)(x) = 2x

(2)(-7) = -14

5x^2 - 35x + 2x - 14

Now combine like terms.

5x^2 - 33x - 14.

This is the right answer because it is now in the form of ax^2 + bx + c
User Kunal Batra
by
4.9k points